Energy Efficiency Analysis and Innovation in Mulia Gading Kencana Housing - Kurniasih, Aqmala Fatma; Barus, Lita Sari (UI Scholars Hub, 2025)
Background: The development of sustainable housing has become an important issue amid global climate change challenges. Although the concept of green housing has begun to be implemented in Indonesia, evaluations of its application in subsidized housing remain limited, particularly those examining design readiness and neighborhood system integration. Aim: This study aims to analyze the implementation of energy efficiency and neighborhood innovation variables within the green housing concept at the Mulia Gading Kencana (MGK) Housing Estate in Serang, Banten. Methods: This research employed a descriptive–quantitative approach with a case study design. Data were collected through field observations, brief interviews with the developer, and a review of Greenship Neighborhood (GBCI) standards and international green building frameworks (LEED, BREEAM, WELL, and EDGE). The assessment applied a Likert-scale, presence-based approach, with a weighting scheme of 60% for energy efficiency and 40% for neighborhood innovation, complemented by a sensitivity check using an alternative 50:50 weighting scheme. Results: The assessment results indicate that MGK achieved a final score of 4.8 under both the 60:40 and 50:50 weighting schemes, demonstrating consistency across different weighting assumptions. The implementation of energy efficiency is reflected in the use of LED lighting across all housing units, the utilization of solar energy for neighborhood lighting, and the application of passive design strategies such as building orientation, cross-ventilation, and shading devices. Neighborhood innovation includes water and waste management systems such as bio-septic tanks, biopores, and artificial lakes, as well as the use of environmentally friendly materials with more than 40% domestic content. Conclusion: Of the 2 variables that have been applied, the maximum score is obtained on the criteria for renewable energy types, passive design strategies, along with innovation in residential areas. This research shows that the concept of green housing can be applied contextually and realistically to subsidized housing through an emphasis on energy efficiency and adaptive regional innovation. Keywords: affordable housing, energy efficiency, green housing, innovation, Greenship Neighborhood